Nanoporous Films and Nanostructure Arrays Created by Selective Dissolution of Water‐Soluble Materials. Issue 11 (13th September 2018) - Kim, Yoon Seo; Song, Jaejung; Hwang, Chihyun; Wang, Xuejing; Wang, Haiyan; MacManus‐Driscoll, Judith L.; Song, Hyun‐Kon; Cho, Seungho
Abstract: Highly porous thin films and nanostructure arrays are created by a simple process of selective dissolution of a water‐soluble material, Sr3 Al2 O6 . Heteroepitaxial nanocomposite films with self‐separated phases of a target material and Sr3 Al2 O6 are first prepared by physical vapor deposition. NiO, ZnO, and Ni1− x Mg x O are used as the target materials. Only the Sr3 Al2 O6 phase in each nanocomposite film is selectively dissolved by dipping the film in water for 30 s at room temperature. This gentle and fast method minimizes damage to the remaining target materials and side reactions that can generate impurity phases. The morphologies and dimensions of the pores and nanostructures are controlled by the relative wettability of the separated phases on the growth substrates. The supercapacitor properties of the porous NiO films are enhanced compared to plain NiO films. The method can also be used to prepare porous films or nanostructure arrays of other oxides, metals, chalcogenides, and nitrides, as well as films or nanostructures with single‐crystalline, polycrystalline, or amorphous nature. Abstract : Nanoporous epitaxial films or substrate‐supported nanostructure arrays are prepared by a simple procedure of dipping nanocomposite films in pure water for 30 s to dissolve a water‐soluble phase, Sr3 Al2 O6 out of nanocomposite films. NiO, Ni0.5 Mg0.5 O, and ZnO are used as model binary systems. The film morphologies are controlled by the relative wettability of the separated phases on the underlying materials.